Media an Inseparable Organ in Promoting Cashless Economy - Dr.Paromita Das; Satarupa Roy; Jyotish Dutta; GP Pandey (Journal of Advanced Research in Journalism & Mass Communication, 2021)
After demonetization, a sudden step taken on November 8th 2016 to reduce corruption in India, the democracy has understood why the Prime Minister stretched on the issue of having a bank account from the moment he was elected. For techno savvy people it was just another day as they hardly use cash for their day to day consumption, even their glossaries are ordered online but for those non-techno savvies that constitute the major portion of the population it was few months of disaster. Even worse was when the news of India moving towards a cashless economy was aired. All of a sudden the non-functional bank accounts got active, shops even the smaller ones got card readers and some corrupt souls left their bodies. This is indeed a brave decision taken by the government and many counties which have already taken this step have prospered and got rid of corruption and black marketing. However, before incorporating this idea into action it is very important to understand what type of population India possesses and will it be feasible for all the people to go cashless. Here the Media, the fourth pillar of democracy can play a great role. Media took a forefront in the past by helping the government with various projects like Krishi Darshan which taught the farmers the use of new technique of farming for better production. However, over the years the role of media has only become confined to reporting and entertaining. The educative power of media has somewhat diminished . However, with time the reach has increased and therefore it can serve as the befitting partner of the government in making India a cashless economy. How to cite this article: Das P, Roy S, Dutta J. Media an Inseparable Organ in Promoting Cashless Economy. J Adv Res Jrnl Mass Comm 2020; 7(3): 16-20.